Characterizing the Transmission Dynamics of the Cases Registered by Covid-19 in Venezuela According to Epidemic Wave and the Value of the Mantissa - Raúl Isea (International Journal of Coronaviruses, 2020)
This work characterizes the transmission dynamics of the cases registered by Covid-19 in Venezuela. The needed input data were obtained from the official gazettes issued by the Government of Venezuela, from March 15 to September 9, 2020. Later, the value of the mantissa was determined, revealing the impact of the different outbreaks with special attention to the events at the baseball stadium in Nueva Esparta State, and the Las Pulgas Market located in Maracaibo. Finally, a mathematical model based on four epidemic waves revealed that the cases are increasing significantly over time after the episode that occurred in the Las Pulgas Market.
Keywords: Covid-19